Analysis of the Covid-19 Pandemic Impact on the Performance of Construction Projects in Denpasar City - Dharmayanti, GAP. Candra; Sudarsana, Dewa Ketut; Pradnyawati, Putu Mas Diah (International Journal of Civil, Mechanical and Energy Science, 2022)
Construction projects in Denpasar City have directly experienced the impact of the Covid-19 pandemic, which has brought about major changes in the construction sector which have been deeply felt by project stakeholders. The impacts include aspects of human resources, materials and equipment, work methods, and finances. The problems described have the potential to affect the performance of construction projects. The purpose of this research is to analyze the impact of the Covid-19 pandemic on the performance of construction projects in Denpasar City and formulate strategies to improve the performance of construction projects that are dominantly affected by the Covid-19 pandemic. Technical analysis of the data was determined using multivariate analysis with data obtained through surveys with online questionnaires and analyzed using SmartPLS software; Focus Group Discussions (FGD) and fishbone diagrams were conducted. The results of this study concluded that the Covid-19 pandemic had an impact on the performance of construction projects in Denpasar City, especially on the human resource aspect in terms of 2.5% time, 0.9% in terms of costs; material and equipment aspects in terms of time 3.0%, in terms of cost 1.2%, in terms of quality 0.1%; aspects of work methods in terms of time 3.4%, in terms of cost 0.7%, in terms of quality 0.7%; and the financial aspect in terms of costs 4.9%, in terms of time 1.5%. The Covid-19 pandemic variable that has the most impact on the performance of construction projects is the material and equipment aspect of 3.321 from the P-value calculation. Strategies to improve the performance of construction projects include providing equivalent alternative materials, studying contracts with suppliers in more detail, re-scheduling, monitoring related to material expeditions, pre-ordering first to suppliers, changing work methods, and seeking to find other heavy equipment service providers.